Haemoglobin level among the regular voluntary blood donors - Hoque, MM; Adnan, SD; Begum, HA; Rahman, M; Rahman, SM; Mamun, MAA; Faruki, MA (Journal of Dhaka Medical College, 2012)
DOI: http://dx.doi.org/10.3329/jdmc.v20i2.10544 J. Dhaka Med. Coll. 2011; 20(2): 168-173